Functional Roles of Farmer Producer Companies: the Stakeholders’ Perception - Ajith, Akhil; Bonny, Binoo P (Journal of Extension Education, 2024)
This study explored the perception of stakeholders of selected Farmer Producer Companies (FPC) of Kerala, India, on the functional role of such companies in the livelihood betterment of farmers. Five roles were identified and ranked based on the percentage scores for understanding the perception of the role of FPCs. The five roles analyzed included facilitate development of member farmers, increase the cultivation of particular crop, identify needs of farmers and conduct trainings/ exposure visits, delivery of services to farmers and creation of more employment among farmers. Based on results it was inferred that stakeholders from various FPCs in the state identified delivery of services to farmers as the most important functional role of FPCs. This was followed by the role of farmer development facilitation which was agreed by over 75 percent of all categories. Creation of more employment opportunities for farmers, and impart of trainings and exposure visits to them was given comparatively less importance by all the stakeholders. The least important role identified was increasing the crop cultivation.